2020
DOI: 10.3390/antibiotics9090565
|View full text |Cite
|
Sign up to set email alerts
|

Vancomycin-Resistant Enterococci (VRE) in Nigeria: The First Systematic Review and Meta-Analysis

Abstract: Vancomycin-Resistant Enterococci (VRE) are on the rise worldwide. Here, we report the first prevalence of VRE in Nigeria using systematic review and meta-analysis. International databases MedLib, PubMed, International Scientific Indexing (ISI), Web of Science, Scopus, Google Scholar, and African journals online (AJOL) were searched. Information was extracted by two independent reviewers, and results were reviewed by the third. Two reviewers independently assessed the study quality using the Preferred Reporting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 62 publications
(62 reference statements)
0
8
0
1
Order By: Relevance
“…Nigeria is the only nation in Africa where a single survey detected VRE in horses [ 35 ]. In a systematic review and meta-analysis, Wada et al [ 40 ] reported 25.3% VRE prevalence in Nigeria. Europe has been the hot spot for VRE since it was first reported in humans in the 1980s [ 7 , 40 , 41 ] and was also the first continent to collectively move for the ban of avoparcin as a growth promoter [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nigeria is the only nation in Africa where a single survey detected VRE in horses [ 35 ]. In a systematic review and meta-analysis, Wada et al [ 40 ] reported 25.3% VRE prevalence in Nigeria. Europe has been the hot spot for VRE since it was first reported in humans in the 1980s [ 7 , 40 , 41 ] and was also the first continent to collectively move for the ban of avoparcin as a growth promoter [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that this compensatory cost may be similar to that previously reported in terms of the possible transfer of virulence-traits and antimicrobial resistance ( Lata et al, 2016 ). However, VREfm is organism of low virulence and low pathogenicity ( Puchter et al, 2018 ; Wada et al, 2020 ), and the beneficial effect on the clinical efficacy of fosfomycin brought about by the attenuated virulence of their strains is much less than the adverse effect on the clinical efficacy of fosfomycin brought about by the high expression of fosfomycin resistance. Therefore, in the face of severe infections where fosfomycin monotherapy may cause a high degree of resistance, the combination of fosfomycin is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…In Ethiopia, Melese et al estimated the prevalence rate to be 14.8% (95% CI: 8.7-24.3) while in Nigeria, Wada et al estimated the prevalence of VRE from 19 original investigations to be 25.3% (95% CI: 19.8-30.8%) Acinetobacter baumannii resistance to antibiotics was also reported by many previous investigations which showed that the prevalence rate of this resistance was hugely variable according to the applied antibiotic per country. 19,20 Pormohammad et al analyzed the results of 150 original investigations in a single meta-analysis to estimate the prevalence rate of cefotaxime and colistin by country. 21 Africa had a 99% prevalence resistance rate to cefotaxime which was the highest while countries in the Western Pacific had the lowest prevalence rate of 1.1%.…”
Section: Chances Of Antibiotic Resistance (Prevalence and Associated mentioning
confidence: 99%